Budaya Aksara Kawi Sunda: (Tinjauan Umum Atas Kodeks dan Fungsi Kodeks dalam Tradisi Sunda Kuno Serta Analisa Paleografi atas Aksara di Teks-Teks Tersebut) - Prastya, Hady (Perpustakaan Nasional RI, 2024)
The bias of the print tradition in Sundanese society is still colored by the assumption that the script on Sundanese lontar has a different form from the script on gebang leaves. In fact, Sundanese script, both in gebang and lontar, is essentially the same. Therefore, this paper will discuss the two codices used in the ancient Sundanese tradition, namely gebang and lontar, and try to prove that these two codices are connected and have continuity. The approach used is philological studies with an emphasis on the use of codicological steps. Because the script is also closely related, a paleographic approach is also used, so that a general picture of the tradition of writing texts in Sunda in the past can be seen. The latest Sundanese script, the Sundanese Baku script, is also mentioned as a comparison, and hopefully an improvement.